1994
DOI: 10.1056/nejm199411103311903
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Nuclear p53 and Tumor Progression in Bladder Cancer

Abstract: In patients with transitional-cell carcinoma confined to the bladder, an accumulation of p53 in the tumor-cell nuclei detected by immunohistochemical methods predicts a significantly increased risk of recurrence and death, independently of tumor grade, stage, and lymph-node status. Patients with transitional-cell carcinoma confirmed to the bladder that demonstrates nuclear p53 reactivity should be considered for protocols of adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
354
9
20

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 731 publications
(408 citation statements)
references
References 16 publications
25
354
9
20
Order By: Relevance
“…In our study, the grade does not appear as an independent prognosis variable. In this aspect, our results are consistent with those included in other multivariate studies, in terms of survival, 6,12,19,21 recurrence, 8,11,[15][16][17][18][19]25 and progression. [21][22][23]25 Our study shows that there are several significant variables in the prognosis of bladder TCC at T1 and T2a classifications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the grade does not appear as an independent prognosis variable. In this aspect, our results are consistent with those included in other multivariate studies, in terms of survival, 6,12,19,21 recurrence, 8,11,[15][16][17][18][19]25 and progression. [21][22][23]25 Our study shows that there are several significant variables in the prognosis of bladder TCC at T1 and T2a classifications.…”
Section: Discussionsupporting
confidence: 92%
“…Esrig et al 19 and Tsuji et al 20 point to a significant link between the expression of p53 and survival, although the latter study included only a univariate analysis. However, in the studies by Jahnson et al 6 and Liukkonen et al 21 the expression of p53 does not appear as an independent variable of survival.…”
Section: Discussionmentioning
confidence: 99%
“…The generally poor prognosis of advanced bladder cancer indicates the need for new therapeutic modalities. Mutations in the p53 gene are the most common genetic defect in human bladder cancer, which occur in approximately 50% of bladder cancer and are associated with highstage, high-grade TCC (Sidransky et al, 1991;Esrig et al, 1994). In accordance with the important role of p53 in bladder carcinogenesis, loss of heterozygosity of 17p, where p53 gene is located, is detected in more than 60% of patients with poorly differentiated tumours (Olumi et al, 1990).…”
mentioning
confidence: 99%
“…Patients with superficial bladder cancer harboring mutations of the TP53 gene and altered patterns of p53 expression have a more aggressive clinical course (11)(12)(13)(14). Several studies reported that detection of altered p53 expression was associated with disease progression and death due to bladder cancer (12,15). Moreover, these aberrations were found to be independent predictors of recurrence and survival in several of the referred studies.…”
mentioning
confidence: 99%
“…Because selection criteria to determine treatment for a particular tumor in a particular patient are incompletely defined, new biologic determinants are needed for proper selection and monitoring of therapy. It has been reported that mutations and altered patterns of p53 expression, or genes involved in the p53 pathways, occur in an important percentage of patients with advanced bladder cancer, ranging from 40 to 70% of these cases (14,15,17,18). Moreover, it has been reported that such alterations may represent a major cause of treat-ment failure and subsequent death (17,18).…”
mentioning
confidence: 99%